Semiotic and Marxian methods: categorical convergences and epistemological questions - Borrelli, Giorgio (E|C, 2020)
Ferruccio Rossi-Landi (1921-1985) proposed to frame certain Marx’s argumentations into a semiotic perspective. On the one hand, Rossi-Landi tried to demonstrate how the analytical instruments developed by the Marxian critique of political economy can contribute to a better understanding of semiotic processes. On the other hand, he attempted to illustrate how a semiotic methodology was present at an early stage in certain fundamental excerpts of Marxian theory; e.g. in the analysis of Commodity-Form. In line with Rossi-Landi’s suggestions, in this paper I will try to establish a dialogue between Marxian method and other semiotic approaches.